Application of Red Dragon Fruit Dyes as Staining in Histological Study - Asra, Ridho; R, Rusdi; Fitrina, Indah Kemala; Nessa, Nessa (Asian Journal of Pharmaceutical Research and Development, 2021)
Background: The betacyanin pigment found in dragon fruit flesh (Hylocereus costaricensis (F.A.C.Weber) Britton & Rose) has many advantages, for instance as a tissue histology dye. Objectives: determining the properties of organs stained with betacyanin red dye and finding alternative histology colors to replace synthetic hematoxylin-eosin dyes. Summary of contents of the article: The flesh of the red dragon fruit (Hylocereus costaricensis (F.A.C.Weber) Britton & Rose) was extracted using the Ultrasonic Assisted Extraction (UAE) method. The study employed six male white mice divided into two treatment groups: a placebo group induced with 1% Na.CMC carrier solution and a positive control group generated a toxic dose of paracetamol. The results were visually compared to hematoxylin-eosin with standard betacyanin and betacyanin extract of red dragon fruit flesh concentrations of 50% (v/v), 80% (v/v), and 100% (v/v). Conclusion: Betacyanin from the flesh of the red dragon fruit can be applied as a histological dye in the liver of male white mice and as a counterstaining hematoxylin as a substitute for eosin dye at a concentration of 100% (v/v).